Amaranth Genomic Resource Database: an integrated database resource of Amaranth genes and genomics - Singh, Akshay; Mahato, Ajay Kumar; Maurya, Avantika; Rajkumar, S.; Singh, A. K.; Bhardwaj, Rakesh; Kaushik, S. K.; Kumar, Sandeep; Gupta, Veena; Singh, Kuldeep; Singh, Rakesh (Frontiers in Plant Science, 2023)
Amaranth (Amaranthus L.) is native to Mexico and North America, where it had been cultivated thousands of years ago, but now amaranth is grown worldwide. Amaranth is one of the most promising food crops with high nutritional value and belongs to the family Amaranthaceae. The high-quality genome assembly of cultivated amaranth species (A. hypochondriacus, A. cruentus) and wild/weedy species (A. tuberculatus, A. hybridus, and A. palmeri) has already been reported; therefore, we developed an Amaranth Genomic Resource Database (AGRDB) to provide access to all the genomic information such as genes, SSRs, SNPs, TFs, miRNAs, and transporters in one place. The AGRDB database contains functionally annotated gene information with their sequence details, genic as well as genomic SSRs with their three sets of primers, transcription factors classified into different families with their sequence information and annotation details, putative miRNAs with their family, sequences, and targeted gene details, transporter genes with their superfamily, trans-membrane domain details, and details of genic as well as non-genic SNPs with 3’ and 5’ flanking sequence information of five amaranth species. A database search can be performed using the gene ID, sequence ID, sequence motif, motif repeat, family name, annotation keyword, scaffold or chromosome numbers, etc. This resource also includes some useful tools, including JBrowse for the visualization of genes, SSRs, SNPs, and TFs on the respective amaranth genomes and Blast Search to perform a blast search of the user’s query sequence against the amaranth genome as well as protein sequences. The AGRDB database will serve as a potential platform for genetic improvement and characterization of this futuristic crop. The AGRDB database will be accessible via the link http://www.nbpgr.ernet.in:8080/AmaranthGRD/.